Blood conservation strategies for reducing peri-operative blood loss in open heart surgery. - Rahman, Z; Hoque, R; Ali, A; Rahman, M; Rahman, MS (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jan;20(1):45-53 The abstract of this article is available on the PubMed website